2020
DOI: 10.1186/s13075-020-02183-2
|View full text |Cite
|
Sign up to set email alerts
|

A unique thymus-derived regulatory T cell subset associated with systemic lupus erythematosus

Abstract: Background: Foxp3 is a marker for regulatory T cells (Treg cells), but recent studies have shown the plasticity and heterogeneity of CD4 + Foxp3 + T cells. This study aimed to examine the phenotype and function of circulating CD4 + Foxp3 + T cells in patients with systemic lupus erythematosus (SLE). Methods: We enrolled 47 patients with SLE, 31 with organ-specific autoimmune diseases (15 with multiple sclerosis and 16 with primary immune thrombocytopenia), and 19 healthy subjects. Peripheral blood mononuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…These findings suggest avenues for the treatment of autoimmunity based on selectively exploiting the exhausted phenotype of tissue-infiltrating T cells in SLE [ 42 ]. Hironari Hanaoka et al [ 43 ] found that CD4 + Foxp3 + IL-17A + cells were infiltrated into the renal biopsy specimens of patients with active lupus nephritis. Liao et al [ 44 ] confirmed through in vivo experiments that renal-infiltrating CD11c + cells are pathogenic in murine lupus nephritis through promoting CD4 + T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest avenues for the treatment of autoimmunity based on selectively exploiting the exhausted phenotype of tissue-infiltrating T cells in SLE [ 42 ]. Hironari Hanaoka et al [ 43 ] found that CD4 + Foxp3 + IL-17A + cells were infiltrated into the renal biopsy specimens of patients with active lupus nephritis. Liao et al [ 44 ] confirmed through in vivo experiments that renal-infiltrating CD11c + cells are pathogenic in murine lupus nephritis through promoting CD4 + T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Interestingly, in recently published data, a unique thymus-derived Treg population was found to be increased in patients with SLE. 46 Hanaoka et al 46 also found infiltration of these Tregs within kidney biopsies from patients with active LN. The results from our comparison to the human single-cell gene expression data indicated a similar finding.…”
Section: Discussionmentioning
confidence: 96%
“…For example, kidney-infiltrating T cells (KITs), as activated effector cells, may cause organ failure and tissue damage (64). CD4 + Foxp3 + IL-17A + cell infiltration was found in renal biopsy specimens of active lupus nephritis (65). Moreover, urinary CD11c+ macrophages expressed proinflammatory cytokines (IL-6 and IL-1) and resembled infiltrated monocytes (66).…”
Section: Discussionmentioning
confidence: 99%